2013
DOI: 10.1021/ic4001957
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of the Initial Stage of Diborane Pyrolysis

Abstract: The rate constants for the association of two boranes to form diborane are investigated using several methods. The most sophisticated method is the variable reaction coordinate-variational transition state theory (VRC-VTST) which has been developed to handle reactions with no enthalpic barriers. The calculated rate constant of 8.2 × 10(-11) cm(3)·molecule(-1)·s(-1) at 545 K is in good agreement with experiment. The rate constant was also computed using conventional VTST with the G4 composite method. Two variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 70 publications
2
13
0
Order By: Relevance
“…The contributions of the bimolecular reactions, 2B 2 H 6 → B 3 H 9 + BH 3 and B 2 H 6 + H → B 2 H 5 + H 2 , must be minor because of their large activation energies. The activation energy for the former reaction has been reported to be 120 kJ mol –1 , while the barrier height for the latter reaction is 61 kJ mol –1 according to our calculation. The unimportance of the latter reaction is also supported by the mass spectrometric observation that the decomposition efficiency of B 2 H 6 is decreased by the addition of H 2 .…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The contributions of the bimolecular reactions, 2B 2 H 6 → B 3 H 9 + BH 3 and B 2 H 6 + H → B 2 H 5 + H 2 , must be minor because of their large activation energies. The activation energy for the former reaction has been reported to be 120 kJ mol –1 , while the barrier height for the latter reaction is 61 kJ mol –1 according to our calculation. The unimportance of the latter reaction is also supported by the mass spectrometric observation that the decomposition efficiency of B 2 H 6 is decreased by the addition of H 2 .…”
Section: Discussionsupporting
confidence: 64%
“…The production mechanism of BH 3 from B 2 H 6 , reaction , is not clear. Both thermal decomposition in the gas phase , and catalytic decomposition on the wire surfaces are possible. Mankelevich and co-workers suggested the importance of gas-phase decomposition rather than the catalytic decomposition, , although the contribution of catalytic decomposition was also mentioned .…”
Section: Discussionmentioning
confidence: 99%
“…The question is how BH 3 is produced. It has been shown that B 2 H 6 can be decomposed thermally in the gas phase [5][6][7][8][9][10][11][12]. Of course, catalytic decomposition on hot wire surfaces can also be expected [12].…”
Section: Introductionmentioning
confidence: 99%
“…At the G4 level, the free energy maximum on the dissociation path of diborane was 6.7 kcal/mol at 420 K larger than two separated BH 3 units. 11 When 6.6 kcal/mol is added to the free energy of B 3 H 7 (c) + BH 3 , the activation free energy B 4 H 10 (a) → B 4 H 8 (d) + H 2 is more favorable by 1.0 kcal/mol than B 4 H 10 (a) → B 3 H 7 (c) + BH 3 at 333 K. The preference does not change at different temperatures as seen in Table 3.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The reaction mechanism can be summarized in Figure 9. Briefly, B 4 H 10 eliminates hydrogen, then B 4 H 8 reacts with 11 , and H 2 ) in the gas mixture were collected after a particular time interval of at least 60 s after the reaction started. Even at the very first experimental point, both H 2 and B 5 H 11 were already produced.…”
Section: ■ Results and Discussionmentioning
confidence: 99%